2000
DOI: 10.1038/81823
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of AMPA receptor endocytosis by a signaling mechanism shared with LTD

Abstract: The endocytosis of AMPA receptors is thought to be important in the expression of long-term depression (LTD) triggered by NMDA receptor activation. Although signaling pathways necessary for LTD induction have been identified, those responsible for the regulated internalization of AMPA receptors are unknown. Here we show that activation of NMDA receptors alone can trigger AMPA receptor endocytosis through calcium influx and activation of the calcium-dependent protein phosphatase calcineurin. A distinct signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

46
641
6
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 667 publications
(697 citation statements)
references
References 51 publications
46
641
6
4
Order By: Relevance
“…In agreement with the electrophysiology data, our results show that NMDAR‐dependent internalisation of GluA2‐containing AMPARs, which is thought to be the major mechanism for LTD (Beattie et al , 2000; Anggono & Huganir, 2012), is unaffected by Ago2 S387 mutations, emphasising that distinct pathways control structural and functional plasticity.…”
Section: Discussionsupporting
confidence: 90%
“…In agreement with the electrophysiology data, our results show that NMDAR‐dependent internalisation of GluA2‐containing AMPARs, which is thought to be the major mechanism for LTD (Beattie et al , 2000; Anggono & Huganir, 2012), is unaffected by Ago2 S387 mutations, emphasising that distinct pathways control structural and functional plasticity.…”
Section: Discussionsupporting
confidence: 90%
“…NMDAR activation induces AMPAR internalization and recycling. This internalization requires the activation of protein phosphatases 13 , one of which is the Ca 2+ -dependent protein phosphatase calcineurin 23 . The crucial dephosphorylated target is still unknown.…”
Section: Activity Drives Removal Of Amparsmentioning
confidence: 99%
“…Some evidence suggests that ligand binding by itself is a trigger for endocytosis 13,14 , but it has also been reported that AMPAR-dependent internalization is caused by an AMPAR-dependent depolarization, which then induces Ca 2+ influx through activation of voltage-gated Ca 2+ channels 14,23,27 , and would presumably act through the same mechanisms as NMDA-induced internalization. The ligand-dependent AMPAR internalization is not dependent on intracellular Ca 2+ and is not accompanied by dephosphorylation of GluR1; notably, AMPARs internalized by this ligand-dependent mechanism are targeted to lysosomes rather than recycled 14 .…”
Section: Activity Drives Removal Of Amparsmentioning
confidence: 99%
See 2 more Smart Citations